PENGELOLAAN KONFLIK STUDI KASUS KEPALA MADRASAH TSANAWIYAH NEGERI 2 JEMBER - Muhammad Shohibul Aqli; Dian Runi Masruroh; Faizatul Malihati; Mu' Alimin (Al Fuadiy Jurnal Hukum Keluarga Islam, 2022)
Conflict is a part of human nature in living togather in the society which by good management it can be used as a stimulus for improving the quality of work performance, especially in Islamic educational institutions. This study examines the source of conflict and the urgency of conflict management in the institutional environment of Islamic education. This research is a library research with a descriptive approach. Conflict management in Islamic educational institutions is an effective way of increasing work productivity. The key of the effectiveness of conflict management in Islamic educational institutions is the ability and innovation of institutional leaders to combine or choose the best among several conflict management strategies such as giving explanation (tabayyun), deliberation, tahkim, ishlah, and other strategies. Therefore, the leaders of Islamic educational institutions must strive to improve the ability, insight, and innovation in managing conflicts in order to improve the quality of work performance optimally.